Collaboration and competition: A social network analysis of Thailandʹs music industry - Wichaya Peechapat; Nattapong Puttanapong (Economies, 2023)
This study quantitatively investigates the collaborative framework and competitive landscape of Thailand's evolving music industry, driven by technological progress and changing consumer preferences. By examining data obtained from Thailand's Department of Intellectual Property, specifically 138,868 songs, it explores the complex network of relationships among music creators, artists, and various rights-holders, including those associated with recording, music, melodies, and lyrics. Utilizing social network analysis, this research uncovers a power law distribution in these networks, reflecting a scale-free market configuration. This characteristic is marked by a few dominant players exercising considerable market influence, contrasted with numerous less-interconnected participants. This investigation notes regular patterns of collaboration between artists and different rights-holders. Furthermore, the network of music creators displays small-world properties, with short collaborative distances fostering efficient information exchange and creative synergy. Crucially, this study identifies key influential players instrumental in directing the industry's major trends, highlighting their role in market concentration. These significant findings will provide critical evidence for informing future policy development aimed at improving efficiency and equity in the digital content industries.
Keywords: 330; music; social network analysis; market concentration; Thailand; small-world phenomenon